Stability of the Thermohaline Circulation to Noisy Surface Buoyancy Forcing for the Present and a Warm Climate in an Ocean General Circulation Model - Skagseth, Øystein; Mork, Kjell Arne (Journal of Physical Oceanography, 1998)
The stabilities of two different circulation regimes in the North Atlantic, 1) the present thermohaline circulation and 2) a weaker thermohaline circulation, are compared using the Hamburg Large Scale Geostrophic (LSG) ocean circulation model. The latter circulation regime is obtained by restoring the LSG model toward an on average 48C warmer air surface temperature corresponding to a doubled atmospheric content of CO 2 . The stabilities of these stationary states are investigated by imposing various amounts of stochastic noise on the surface freshwater flux. The simulations show more variability on secular timescales for the present than for the warm climate. Since the modeled static stabilities for the two climates are relatively similar, the different rates of variability are probably connected to other mechanisms. In the present climate at high latitudes the two buoyancy fluxes due to heat and freshwater are of similar magnitudes but with opposite signs; thus switches between convective and nonconvective periods at secular timescales are possible. In the warm climate the buoyancy flux due to heat dominates. This compensates the effect of the noisy freshwater forcing and thus reduces the potential for secular oscillations. The stronger coupling between the Atlantic and the Southern Ocean for the present relative to the warm climate could also contribute to this difference. Furthermore, the simulations show that the variability of the Antarctic Circumpolar Current transport for the present climate exceeds that of the warm climate. For increasing stochastic noise the present circulation approaches that of the warm circulation. The authors apply a mixture of heat flux and temperature restoring for the surface boundary condition. Comparison with similar works, which apply a pure restoring for surface temperature, shows that the ocean circulation is much less sensitive to forced stochastic freshwater anomalies with the type of boundary condition used herein. A box model is used to illustrate the effects of the surface temperature parameterizations and the different buoyancy forcing for the present and warm climate.
Keywords: AABW; Sørishavet; Sørishavsstrømmen; geofysikk; havstrømmer; oseanografi; polarområdene; vannmasser

Hot water drilling near Filchner station, Ronne ice shelf - Orheim, Olav; Østerhus, Svein; Melvold, Kjetil; Eiken, Trond; Thomsen, Henrik Højmark; Winther, Jan-Gunnar; Bævre, Halvor (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Antarktis; NARE 1992/93; glasiologi; havstrømmer; isshelf; oseanografi; vannmasser

Modelling the ocean response to secular surface temperature transitions - Mork, K. A.; Skagseth, Øystein (Climate Dynamics, 1996)
The ocean response to surface temperature transients is simulated with the use of the Hamburg large-scale geostrophic (LSG) ocean general circulation model (OGCM). The transition, from the present to a climate corresponding to a doubling of the atmospheric CO2 content, is compared with the reversed transition. For the Atlantic, the time scale for the deep ocean to adjust to the temperature changes was similar for both transitions. In the Pacific, the time scale is shorter for the present to warm transition than for the reverse case, a result of increased production of Antarctic bottom water (AABW) during the warm climate. While the transition from cold to warm climate shows no secular variability, the reversed transition generates considerable variability on time scales of 300–400 years. For the warm climate, oscillations with periods of 45 years are found in the Southern Ocean. Results of principal oscillation pattern (POP) analysis indicate that these oscillations are due to interaction between convection in the Southern Ocean and advected salinity anomalies in the Antarctic Circumpolar Current (ACC) and the Southern Pacific Ocean.
Keywords: AABW; Sørishavet; Sørishavsstrømmen; geofysikk; havstrømmer; oseanografi; vannmasser

Modelling of Deep-Sea Gravity Currents Using an Integrated Plume Model - Alendal, Guttorm; Drange, Helge; Haugan, Peter M (The Polar Oceans and Their Role in Shaping the Global Environment, 1994)
An integrated plume model is used to describe large scale gravity currents in the ocean. The model describes competing effects of (negative) buoyancy, friction, entrainment and Cariolis farce, as well as a pressure term due to variable plume thickness, on the flux, speed and flow direction of the plume. Equations for conservation of salt and internal energy (temperature) and a full equation of state far seawater is included in the model. The entrainment of ambient water is parameterized with support in empirical data, and a drag coefficient consistent with the entrainment is introduced. The model is tested against the overflow through the Denmark Strait, the flow down the Weddell Sea continental slope, and the outflow of saline water through the Gibraltar Strait and from the Spencer Gulf, Australia. The farmer gain an extra driving mechanism due to the thermobaric effect, while in the two latter cases the initial density difference is so large that this effect is not essential. Order of magnitude fit with measurements requires drag coefficient between 0.01 and 0.1. Conditions susceptible to meander behaviour and a singularity arising from the pressure dependency on the current thickness variations are briefly discussed.
Keywords: Sørishavet; Weddellhavet; havbunnen; havstrømmer; klimamodeller; oseanografi

Notes on Southern Ocean hydrography, sea-ice and bottom water formation - Foldvik, Arne; Gammelsrød, Tor (Palaeogeography, Palaeoclimatology, Palaeoecology, 1988)
The Southern Ocean circulation and sea-ice distribution is briefly described. The formation of extremely cold bottom water in the Weddell Sea and its relation to the floating Ronne-Filchner Ice Shelves is discussed. It is shown that a concentrated swift eroding bottom current with anomalous low ratio transports the cold and dense ice Shelf Water from the shelf towards large depths. Comments are made on possible implications of this process for the large-scale deep-water circulation and for the interpretation of sediment cores.
Keywords: Sørishavet; Weddellhavet; geofysikk; havis; havstrømmer; hydrografi; isshelf; oseanografi

Circulation and Water Masses on the Southern Weddell Sea Shelf - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Oceanology of the Antarctic Continental Shelf, 1985)
Keywords: Sørishavet; Weddellhavet; forskning; havstrømmer; oseanografi

Physical oceanography studies in the Weddell Sea during the Norwegian Antarctic Research Expedition 1978/79 - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Polar Research, 1985)
Keywords: Sørishavet; Weddellhavet; havstrømmer; hydrografi; isshelf; oseanografi

Bottom Currents Near the Continental Shelf Break in the Weddell Sea - Foldvik, Arne; Kvinge, Thor; Tørresen, Tor (Oceanology of the Antarctic Continental Shelf, 1985)
Keywords: Sørishavet; Weddellhavet; bunnvann; havstrømmer; kontinentalsokkel; kontinentalsokler; tidevannsstrømmer

Measurements of ocean current and bottom pressure near Bouvetøya, January–March 1979 - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; havstrømmer; oseanografi

Tidal currents off the antarctic ice barrier, Queen Maud Land - Sverdrup, Harald Ulrik (Archiv für Meteorologie, Geophysik und Bioklimatologie, Serie A, 1954)
Observations of tidal currents in lat. 71° 01′ S, long. 10° 55′ W indicate that a semi-diurnal tidal wave progresses towards the WSW, that is, parallel to the main direction of the barrier. ForM2 the cotidal hour appears to be about 7h, in good agreement with the value 6.7h, that is derived from observations of the atmospheric pressure. Furthermore, the current measurements indicate that the ratio(K1+O1)/(M2+S2) is large, perhaps as large as 2.5.
Keywords: Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; Sørishavet; havstrømmer; klimaendringer; meteorologi; oseanografi; tidevann

The currents of the coast of Queen Mauds Land - Sverdrup, Harald Ulrik (1953)
Keywords: Dronning Maud Land; glasiologi; havstrømmer; isshelf

Wie entsteht die Antarktische Konvergenz? - Sverdrup, Harald Ulrik (Annalen der Hydrographie und Maritimische Meteorologie, 1934)
Keywords: Sørishavet; forskning; havstrømmer; meteorologi; oseanografi